Peran anggota keluarga pada usaha pemeliharaan ternak sapi potong di Kelurahan Makalonsouw Kecamatan Tondano Timur - Takasenserang, S; Lombogia, S O. B; Malingkas, J A; Sajow, A A (ZOOTEC, 2021)
THE ROLE OF FAMILY MEMBERS INÂ  CATTLE RAISING IN MAKALONSOUW VILLAGE EAST TONDANO DISTRICT This study aims to find out the role of family members in the business of keeping beef cattle, as well as the role of family members to access information, institutional aspects of control aspects, aspects of decision making, and aspects of benefits. This research was conducted in Makalonsow Subdistrict, East Tondano in September - October 2019. Types of survey research using qualitative methods. Data collection through interviews using a coesioner to family members of breeders. The selection of sample respondents was determined deliberately purposive, and variable measurement was carried out using the Guttman Scale measuring instrument, the measurement is scored on each answer. The results showed the role of the family to access information from counseling activities, namely the role of husband 100%, the role of wife 0%, access institutions in counseling in the Village Makalonsow Tondano Timur, the role of husband 100%, wife 0%, aspects of control in the maintenance of beef cattle, namely in the activities of cleaning cages, husband 100%, bathing activities of cattle, husband 96.67% children 3.33%, activities of feeding and drinking to beef cattle, husband 60% wife 26.67% and children 13.33% , aspects of farmer decision making in seed purchasing activities, husband 100%, livestock sales, husband 93.33% wife 6.67%, husband's livestock purchase 100%. Based on the results of the study, showed the head of the family played an important role in the business of keeping beef cattle in Makalonsow Village, East Tondano District.